2018
DOI: 10.1029/2018gl079255
|View full text |Cite
|
Sign up to set email alerts
|

Saturn's Atmosphere at 1–10 Kilometer Resolution

Abstract: We present images of Saturn from the final phases of the Cassini mission, including images with 0.5 km per pixel resolution, as high as any Saturn images ever taken. Notable features are puffy clouds resembling terrestrial cumulus, shadows indicating cloud height, dome and bowl shaped cloud structures indicating upwelling and downwelling in anticyclones and cyclones respectively, and filaments, which are thread‐like clouds that remain coherent over distances of 20,000 km. From the coherence of the filaments, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Two sets of extremely long, curved features were detected near the edges of a southwestern extension of a dark blue-gray region associated with high 5-μm radiances at the southern edge of the NEB. Long, sinuous parallel streaks were detected, some with nearly sinusoidal lateral variability, that were analogous to features observed by the highest-resolution imaging of Saturn's atmosphere by Cassini (Ingersoll et al, 2018). No waves were detected south of 7°S that were not associated with larger vortices, such as the GRS.…”
Section: Discussionsupporting
confidence: 63%
“…Two sets of extremely long, curved features were detected near the edges of a southwestern extension of a dark blue-gray region associated with high 5-μm radiances at the southern edge of the NEB. Long, sinuous parallel streaks were detected, some with nearly sinusoidal lateral variability, that were analogous to features observed by the highest-resolution imaging of Saturn's atmosphere by Cassini (Ingersoll et al, 2018). No waves were detected south of 7°S that were not associated with larger vortices, such as the GRS.…”
Section: Discussionsupporting
confidence: 63%
“…11.11 appears to be the most prominent of the stratospheric layers). There have also been shadows observed in the north polar region (Ingersoll et al, 2018), but these seem to be more subtle for reasons that remain to be understood. Sromovsky et al (2021) also showed that slightly better fits of north polar cloud structure can be obtained in some cases with thicker sheet clouds in which the top pressures are 60% of the bottom pressures (vs. the 90% they used generally).…”
Section: Vertical Extent Of Aerosol Layersmentioning
confidence: 99%
“…3). This spot is possibly the vortex labelled as "A1" in the high-resolution Cassini ISS images obtained during Cassini's Grand Finale (Figure 1 in Ingersoll et al 2018) and is the subpolar single vortex described by del . The vortex is also highlighted in the Cassini map in 2016 shown in Figure 2.…”
Section: Ribbon and Bright Features In 2018 (Ls=99-105)mentioning
confidence: 91%